100 Great Thinkers - Bromberg, Murray [et al.]; Edited by Greene, Jay Elihu (New York Pocket Books, 1969)
Brief Biographies of the great men of thought from Hammurabi to Sartre.
Include Index
Keywords: Biography -- Philosophy